A framework for assessing the blue equity of social-ocean systems in marine governance transformation - Chen, Mingbao; Wang, Yuhao; Xu, Zhibin (Frontiers in Marine Science, 2024)
Fairly utilizing marine resources and maintaining a healthy and sustainable marine ecosystem are crucial for advancing United Nations sustainable development goals and promoting the welfare of all humanity. This article proposed a blue equity assessment framework based on environmental justice theory and related studies. This framework focuses on distributional equity, procedural equity, recognitional equity, and contextual equity within social-ocean systems (SOSs). Its goal is to evaluate and quantify fair practices in the utilization of marine resources and ecosystem services. We analyze the synergistic impact of blue equity on the majority of Sustainable Development Goals (SDGs) by combining peer-reviewed articles and logical judgments. And examine the pathways and mechanisms of influence based on four dimensions of equity, demonstrating the blue equity assessment framework in the SOSs. The blue equity evaluation methodology demonstrates the practical capability of analyzing pathways and influence mechanisms in the SOSs based on four dimensions. The findings seek to enhance the understanding of blue equity concerns in society to guide policymakers in prioritizing blue equity in the utilization and conservation of marine resources and advancing the transformation of global ocean governance.